Electric field modulation of reversible and non-volatile magnetic anisotropy transition in (0 1 1) 0.7[Pb(Mg1/3Nb2/3)O3]–0.3[PbTi0.3O3]/FeSi heterostructures. (24th July 2017) - Guo, Xiaobin; Cui, Baoshan; Guan, Chaoshuai; Li, Dong; Wu, Kai; Yun, Jijun; Wang, Tao; Peng, Yong; Zuo, Yalu; Xi, Li
Abstract: Electric-field-modulated magnetic properties are investigated on FeSi films with a (0 1 1) preferred orientation on (0 1 1) 0.7[Pb(Mg1/3 Nb2/3 )O3 ]–0.3[PbTi0.3 O3 ] (PMN–0.3PT) single crystal substrates. When saturated and reversed coercive electric fields are alternately applied to the Pt/PMN–0.3PT/FeSi/Ta heterostructures, a reversible and non-volatile magnetic transition between four-fold and two-fold anisotropy is demonstrated by means of the angular dependence of remanent magnetization measurements. Based on the electric field control of the 90° magnetic easy axis direction transition of the FeSi film, we also achieve electric-field-mediated giant 180° magnetization switching with the assistance of the magnetic field pulse.